Weed control efficacy and soil activity of a new promising bioherbicide ‘WeedLock’ - Mahmudul Hasan,; Anis Syahirah Mokhtar,; Khairil Mahmud,; Adam Mustafa Rosli,; Hafizuddin Hamdan,; Mst. Motmainna,; Muhammad Saiful Ahmad-Hamdani, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The development of plant-based bioherbicides has gained the interest of researchers and acceptability from the farmers to control weeds in order to reduce their overdependence on chemical herbicides. Therefore, this research investigated the efficacy and soil activity of WeedLock, a new plant-based bioherbicide. In the efficacy study, WeedLock was applied at 672.75, 1345.50 (recommended dose), 2691.00 L ha-1 over the untreated (control) on weeds in mixed-culture (Ageratum conyzoides L., Eleusine indica (L.) Gaertn., and Cyperus iria L). For soil activity, Zea mays L. seedlings were grown in different soil textures, namely clay, sand, sandy clay loam, and peat soil and WeedLock was applied to each soil type at 1345.50 L ha-1 with a pipette as a soil drench method. After 21 days, the plants were harvested, including roots and the soil in trays that were previously sprayed with WeedLock, and the trays were further maintained for 1, 2, 4, 8, 12 and 16 weeks, respectively, before new seedlings were grown on the same soil. WeedLock at 1345.50 L ha-1 showed severe injury on weeds and produced 98.15% weed control efficacy compared to untreated (control). For soil activity, WeedLock did not show any significant decrease in growth and development of Z. mays, and the injury scale was 1.00, which means all leaves of Z. mays remained green, and the plants were actively growing on the WeedLock treated soils. Thus, it can be concluded that WeedLock has excellent weed control efficacy with negligible soil activity.